Modeling of a commercial fuel cell (PEM) usind equivalent electrial model - Holdefer, Antonio Eliseu; Pereira, Andressa Santos; Lima, Luan Marcel de Sousa; Soares, Mateus Parreira; Nogara, Yuri Freitas (Revista Hipótese, 2018)
The world is undergoing an unprecedented technological advance with the everincreasing demand for renewable energy that does not harm the environment on a global scale. Thus, the production of energy from fuel cells is a great alternative for future generations, because it is a "clean", non-polluting energy. The fuel cell is becoming an alternative because it is an electrochemical device where the conversion of chemical energy into electrical energy occurs without any emission of polluting gases. Fuel cells are used in different industries, such as automotive and cogeneration in hospitals and industries. This work has the purpose of modeling the fuel cell of the PEM type (polymeric cell membranes) electrically, that is, an electric circuit scheme developed in the simulation software Proteus presents I x V (voltage-current) and P x I (power-current) curves very similar to the commercial model, thus making simulated fuel cell behavior very similar to the real one. The use of a such model is very beneficial for power electronics engineers who in many cases have the task of designing power converters working in conjunction with fuel cells for different load conditions. The modeling is based on the use of conventional electronic components easily found in simulation software and in the market. The model developed in the present article can be used for both hydrogen and bio-fuels fuel cells such as ethanol, since both operate in a similar way and have similar curves. The model can also be physically built to simulate fuel cell operation for students and engineers. The present article presents an example of the development of a generic model and its use in a commercial 1000W fuel cell.
Keywords: Fuel cell; PEMFC; Electric schematic; PROTEUS